The Effects of COVID-19 Lockdown 1.0 on Working Patterns, Income, and Wellbeing Among Performing Arts Professionals in the United Kingdom (April–June 2020) - Spiro, Neta; Perkins, Rosie; Kaye, Sasha; Tymoszuk, Urszula; Mason-Bertrand, Adele; Cossette, Isabelle; Glasser, Solange; Williamon, Aaron (Frontiers in Psychology, 2021)
Please see abstract in text.